The corrected medicinal form of common tansy flowers reason - R. V. Yakusevich (Бюллетень сибирской медицины)
The results of investigation of the corrected medicinal form on the base of common tansy flowers in this article are represented. The optimal base — syrup of sugar and corrective (composition «orange») was chosen. Some physical-chemical data (capacity, chemical compound, refraction data) are shown.